Application of multi-component fluid model in studies of the origin of skin burns during electrosurgical procedures. Issue 13 (3rd October 2021) - Radmilović-Radjenović, Marija; Sabo, Martin; Radjenović, Branislav
Abstract: This paper reports on safety challenges regarding spark created when the applied electric field exceeds the dielectric breakdown strength as a source of complication during electrosurgery. Despite the unquestionable benefits of electrosurgery, such as minimal chances of infection and fast recovery time, the interaction of the electrosurgical tool with the tissue may result in tissue damage and force feedback to the tool. Some risks of complications often depend on a surgeon's knowledge of instruments and safety aspects of technical equipment that can be eliminated by clarifying the causation and conditions of their development. Current trends in electrosurgery include computational algorithms and methods to control the effect of delivered energy to the patient. For this study, calculations were performed by using the COMSOL simulation package based on a multi-component plasma fluid model. The emphasis is put on conditions that lead to the breakdown of the dielectric medium. It was found that breakdown occurs most easily when both electrodes are cylindrical. For configurations with one or two spherical electrodes, breakdown voltages are higher up to 25% and 48%, respectively. With decreasing the cathode radius, the breakdown voltage may decrease even to 41%. On the other hand, the temperature increase lowers the breakdown voltage. Also, electrical asymmetries appear to be a response to the non-symmetry of the electric field between the electrodes causing differences in the breakdown voltage between 36% and 70%. The results presented here could be very useful for the design of surgical devices to prevent potential complications of electrosurgical procedures.